Affect, Creativity and Migrant Belonging. (20th April 2022) - Wilding, Raelene; Winarnita, Monika
Abstract: Affect and creativity are proposed as offering an important lens for examining the politics of belonging in the everyday lives of migrants and refugees. Mobile emotions are circulated, intensified, and transformed in creative ways through digital media, demanding attention to new opportunities for challenging hierarchies, creating belonging, transforming gendered structures, and reinforcing the foundations of inequality and exclusion.